Knowledge, Perception, and Practices on the Labelling of Dispensed Medicine among Community Pharmacists and General Practitioners in the State of Sarawak, Malaysia - Bin Said, Luqman Nulhakim; Chyi, Loo S.; Anak Talin, Benodict Apok; Foo Khiong, Augustine Law; Mohamad Rosli, Izzah Alia Binti; Pei Sze, Jessica Low; Abdul Razak, Ridhwan bin (Current Drug Safety, 2024)
Background: The labelling of dispensed medicines (LDM) ensures that optimum therapeutic treatment levels are achieved, and medication errors are prevented. In Malaysia, LDM is enforced under the Poisons Act 1952. Objective: To explore the knowledge, perception, and practices of community pharmacists (CP) and general practitioners (GP) on LDM. Methods: A cross-sectional study was conducted from April 2019 until March 2020 among CP and GP practising in Sarawak, Malaysia. Sample sizes were 90 and 150 for CP and GP, respectively. Proportionate stratified random sampling was employed. A self-administered structured questionnaire pre-tested and pilot-tested was used to explore knowledge and perception. Practices were assessed by having participants prepare dispensed medicine labels (DML) using simulated prescriptions. Results: 250 participants; 96 CP and 154 GP participated. While most of them perceived that they knew the requirements of LDM (n = 244; 97.6%), their median knowledge score was poor (57.1%). The mean knowledge score of CP (62.0%) was significantly higher (P = 0.002) than GP (51.0%). The majority of participants perceived that LDM is important (n = 237; 94.8%) and necessary (n = 239; 95.6%) and perceived that poor compliance with the requirements would lead to medication errors (n = 243; 97.2%). Although their knowledge was poor, their median practice score (100.0%) was excellent. There was no correlation between knowledge and perception with the practice of LDM. Conclusion: The majority of CP and GP perceived that LDM is important. Interestingly, although their knowledge of the requirements of LDM was poor, their practices were sound.
Keywords: median knowledge